2019
DOI: 10.3390/su11164277
|View full text |Cite
|
Sign up to set email alerts
|

Environmental vs. Social Responsibility in the Firm. Evidence from Italy

Abstract: Sustainable behavior should necessarily benefit both the environment and society. However, we cannot take for granted that socially responsible firms are also environmentally responsible—e.g., a firm might benefit its stakeholders while degrading the environment—and the reverse applies too—e.g., an environmentally responsible firm might disrespect its employees. Consequently, our purpose is checking whether social responsibility and green investments—proxying for a firm’s environmental responsibility—are compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 89 publications
1
9
0
Order By: Relevance
“…For the EU15, the coefficients were highly significant and positive, showing that the odds of not going beyond environmental legislation is higher for older enterprises. Our findings are consistent with Ferri and Pini [70], who found a higher probability for older firms in Italy to make green investments and thus become more environmentally responsible. For the EU-MNS13 sample, the coefficients for age were positive but not significant, underlying that SMEs with longer business experience are more willing to go beyond legal requirements for environmental responsibility.…”
Section: Econometric Model Of Cer For Smes From Eu15 and Eu-nms13 Cousupporting
confidence: 92%
“…For the EU15, the coefficients were highly significant and positive, showing that the odds of not going beyond environmental legislation is higher for older enterprises. Our findings are consistent with Ferri and Pini [70], who found a higher probability for older firms in Italy to make green investments and thus become more environmentally responsible. For the EU-MNS13 sample, the coefficients for age were positive but not significant, underlying that SMEs with longer business experience are more willing to go beyond legal requirements for environmental responsibility.…”
Section: Econometric Model Of Cer For Smes From Eu15 and Eu-nms13 Cousupporting
confidence: 92%
“…Table 5 shows the values relating to the macro-regional distribution. The choice to carry out this subdivision derives from the marked differences existing among Italian regions, as underlined by numerous authors such as Felice, Garofoli, Scott, and Garofoli [75][76][77]; according to the purposes of the research, the aim is to check whether there are statistically significant discrepancies from the point of view of the Sustainable Development Goals in order to test if values within the entire population of listed Italian companies are similar or different considering the same population but split in two well-segmented samples from a geographical point of view [89][90][91]. In Table 5 the "zero gunger goal" has the same evaluation, statistically significant and positive both for the whole sample and for the two sub-samples.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies examined the relationship between environmental effort and CSR and found a positive relationship between them. For example, Ferri and Pini [21] examined the relationship (i.e., complements, substitutes, or unrelated) between green investments and social responsibility using data from Italian manufacturing firms. They measured a firm's CSR intensity as the average of the six dummy variables indicating relationships with stakeholders, such as employees, other firms, universities and research centers, institutions, banks and trade associations, non-government organizations (NGOs), and consumers.…”
Section: Literature Reviewmentioning
confidence: 99%